Impact of leaf age on common fig susceptibility to rust caused by Cerotelium fici - Vieira-Júnior, José Roberto; da Silveira, Silvaldo Felipe; Vieira-Faria, Ana Beatriz; Aparecida Rodrigues, Luciana; Santos Caetano, Luiz Carlos (Revista Ceres, 2025)
Rust caused by Cerotelium fici leads to significant defoliation in common fig trees (Ficus carica). However, studies on its epidemiology remain scarce. The aim of the present study is to investigate common fig rust progress in leaves inoculated at different ages over two growing seasons (dry and rainy) in an experimental fig orchard. Artificially inoculated leaves and those exposed to natural infection showed more severe rust symptoms when they were inoculated earlier - up to 45 days after leaf emergence. Disease severity and leaf longevity (in days) were inversely and directly proportional to leaf age at inoculation time, respectively. Leaves inoculated at earlier presented significantly higher disease progression rates based on number of pustules per cm², broader area under the disease progress curve (AUDPC) recorded for pustule density and higher maximum severity, which was visually estimated as the percentage of lesioned leaf area. Inoculated young leaves abscised 40 to 60 days earlier than the uninoculated leaves, which were protected from natural infection by plastic bags. The uninoculated leaves remained attached to the plants from 90 to 100 days. These findings highlight apical sprouts as primary targets for protective fungicide applications, which must be more intense at early growing season in order control rust in common fig crops.